Cationic copolymer augments membrane permeabilizing activity of an amphiphilic peptide. Issue 10 (13th August 2017) - Sakamoto, Wakako; Ochiai, Takuro; Shimada, Naohiko; Maruyama, Atsushi
Abstract: Membrane disruptive peptides (also called membrane fusogenic peptides) have been employed for cytosolic delivery of macromolecules such as nucleic acids and proteins. We reported previously that the cationic graft copolymer, poly(allylamine)- graft -dextran (PAA- g -Dex), augments membrane disruptive activity of the negatively charged E5 peptide. Strong membrane disruptive activity was observed in the presence of the copolymer at both acidic and neutral pH. In this paper, activities of E5/PAA- g -Dex mixture were further explored. Membrane permeabilization activity of E5/PAA- g -Dex was dependent on concentrations of both E5 and PAA- g -Dex, indicating that a complex between E5 and PAA- g -Dex produced the activity. Since the activity of peptide/PAA- g -Dex was peptide sequence-specific, we reasoned that PAA- g -Dex activated membrane-permeabilization activity by facilitating folding of E5 into its active conformation. The membrane permeabilization activity of E5/PAA- g -Dex resulted in transportation of bovine serum albumin into HL-60 cells with less cellular toxicity than digitonin, a naturally occurring surfactant used for delivery of macromolecules into cells.